Phytochemical Screening and In Vitro Antibacterial Activity of Methanol and Aqueous Extracts of Acalypha Racemosa Leaves - Chrinius Hammuel; Benedicta P. Anyim; Helen H. Raplong; Victory U. Inekwe; Musa L. Batari (Graduate Program of Syiah Kuala University, 2014)
Abstract - Drug resistance microorganisms have posed enormous public concern there is therefore a need to screen plants that could have the potency in the control of the pathogenic organisms. The extracts obtained from the Acalypha racemosa were screened for phytochemical properties and in vitro investigation of methanol and aqueous extracts. The phytochemical screening revealed the presence of saponins, phlabatanins, flavonoids, and alkaloids. Glycoside and cardiac glycoside, tannins and sterols were in traced amount. The in vitro antibacterial investigation of the crude extract was conducted. The studies showed that the plant contains compounds that have antibacterial activity. The extracts revealed greater potential against the test bacteria with zones of inhibition ranging from 20-30 mm for methanol extract in the order Escherichia coliKlebsiella pneumoniaeProteus mirabilisBacillus subtilisPseudomonas aeruginosa and 18-27mm for aqueous extract in the order Escherichia coli Bacillus subtilis Klebsiella pneumoniae and Pseudomonas aeruginosa Proteus mirabilis. All the bacteria were more susceptible to methanol extract than the aqueous extract as indicated in the zones of inhibition with exception of Pseudomonas aeruginosa in which there was no inhibition. The aqueous extract had effect on all the test bacteria although having zones of inhibition lower than the methanol extract. The minimum inhibitory concentration (MIC) of both extracts range from 12.5-50 mg/ml and the minimum bactericidal concentration (MBC) range from 25-100 mg/ml. Escherichia coli was more susceptibility to both extracts and less was seen in the case of aqueous extract against Proteus mirabilis. The screening of the plant has revealed its potency in the treatment of pathogenic infections that may be caused by these pathogens.